Pharmacogenomics of Hypertension: A Genome‐Wide, Placebo‐Controlled Cross‐Over Study, Using Four Classes of Antihypertensive Drugs. Issue 1 (12th May 2015) - Hiltunen, Timo P.; Donner, Kati M.; Sarin, Antti‐Pekka; Saarela, Janna; Ripatti, Samuli; Chapman, Arlene B.; Gums, John G.; Gong, Yan; Cooper‐DeHoff, Rhonda M.; Frau, Francesca; Glorioso, Valeria; Zaninello, Roberta; et al.
Abstract : Background: Identification of genetic markers of antihypertensive drug responses could assist in individualization of hypertension treatment. Methods and Results: We conducted a genome‐wide association study to identify gene loci influencing the responsiveness of 228 male patients to 4 classes of antihypertensive drugs. The Genetics of Drug Responsiveness in Essential Hypertension (GENRES) study is a double‐blind, placebo‐controlled cross‐over study where each subject received amlodipine, bisoprolol, hydrochlorothiazide, and losartan, each as a monotherapy, in a randomized order. Replication analyses were performed in 4 studies with patients of European ancestry (PEAR Study, N=386; GERA I and II Studies, N=196 and N=198; SOPHIA Study, N=372). We identified 3 single‐nucleotide polymorphisms within the ACY3 gene that showed associations with bisoprolol response reaching genome‐wide significance ( P <5×10 −8 ); however, this could not be replicated in the PEAR Study using atenolol. In addition, 39 single‐nucleotide polymorphisms showed P values of 10 −5 to 10 −7 . The 20 top‐associated single‐nucleotide polymorphisms were different for each antihypertensive drug. None of these top single‐nucleotide polymorphisms co‐localized with the panel of >40 genes identified in genome‐wide association studies of hypertension. Replication analyses of GENRES results provided suggestive evidence for a missense variant (rs3814995) in the NPHS1 (nephrin) gene influencing losartan response, and for 2 variants influencing hydrochlorothiazide response, located within or close to the ALDH1A3 (rs3825926) and CLIC5 (rs321329) genes. Conclusions: These data provide some evidence for a link between biology of the glomerular protein nephrin and antihypertensive action of angiotensin receptor antagonists and encourage additional studies on aldehyde dehydrogenase–mediated reactions in antihypertensive drug action.